Changing spaces, expanding mindsets: Towards L2 literacies on a multimodal reading comprehension course - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Heidi Vaarala Juha Jalkanen Language Centre, University of Jyväskylä, Finland   ABSTRACT Recent studies in the field of new literacies have indicated that a remarkable change in the way we access, consume and produce information has taken place. The boundaries between concepts such as authorship and ownership have become blurred. The repertoire of texts available to language learners is almost unlimited. One important purpose of language education is to provide students with functional tools to take advantage of these resources. In this article we discuss the benefits and challenges of teaching L2 reading comprehension in a multimodal learning environment from the perspective of course design. In addition, we attempt to find answers to the following questions: what kinds of assignments are meaningful from the learner's perspective, and what added value does multimodality bring to a learning situation? A design-based research approach was implemented in this study in order to enable a dialogue between theory and practice. The students attending the reading comprehension course described in the article were advanced university students from various European countries, who studied Finnish as a second language. In comparison to traditional reading comprehension courses, it seems that L2 learners benefit from reading digital texts and using a web-based learning platform. The digital environment enabled the learners to read meaningful texts and to actively learn through texts and assignments. Moreover, the web-based learning environment enhanced the flexibility of the learning event - flexibility in terms of time, place, course content, and the learners' language proficiency. However, the course feedback did not support the view that students would automatically be on the "better" side of the digital divide. Instead, they do need assistance in order to understand the new learning mindsets and especially learner autonomy.